Content validation of Guided Reflection in Clinical Nursing Education (GRCNE) module. - Azmi, Barkhis; Atan, Ashikin; Mohd Ali, Noor Azizah; Lee, Siew Pien; Zolkefli, Yusrita; Abdul Maulud, Zamzaliza (Universiti Kuala Lumpur, 2024)
Reflective practice is an essential learning process that enhances critical thinking, adaptation and problem-solving skills among nursing students to face the ever-evolving healthcare system. The Guided Reflection in Clinical Nursing Education (GRCNE) module is developed as part of the effort to empower nurse educators of the nursing training institutions, Ministry of Health, Malaysia to nurture this practice among students in clinical settings. The module is designed to provide a comprehensive and interactive learning experience, focusing on the theoretical foundations, practical application and facilitation of reflective practice in clinical nursing education. This paper presents the content validation of the newly developed GRCNE module involving seven (7) national and international experts with diverse expertise in nursing, education and module development. The content validity achievement (CVA) was calculated and comments on the module were assembled. The GRCNE module scored 85.1% of CVA with individual item scores ranging from 77.1% to 91.4%. The experts further supported the module’s efficacy in the open-ended section, with unanimous agreement on its clear and effective presentation. Some amendments were made based on their constructive feedback to enhance real-world applicability. Overall, the GRCNE module shows great promise for enhancing the teaching practices of nurse educators and promoting the integration of reflective practice in nursing education.